Automate The Boring Stuff With Python : practical programming for total beginners - Sweigart, Al. (San Francisco: No Starch Press, 2020)
If you've ever spent hours renaming files or updating hundreds of spreadsheet cells, you know how tedious tasks like these can be. But what if you could have your computer do them for you. In this fully revised second edition of the best-selling classic Automate the Boring Stuff with Python, you'll learn how to use Python to write programs that do in minutes what would take you hours to do by hand--no prior programming experience required. You'll learn the basics Python and explore Python's rich library of modules for performing specific tasks, like scraping data off websites, reading PDF and Word documents, and automating clicking and typing tasks. Step-by-step instructions walk you through each program, and updated practice projects at the end of each chapter challenge you to improve those programs and use your newfound skills to automate similar tasks.
Python programming basics. Python basics ; Flow control ; Functions ; Lists ; Dictionaries and structuring data ; Manipulating strings -- Automating tasks. Pattern matching with regular expressions ; Input validation ; Reading and writing files ; Organizing files ; Debugging ; Web scraping ; Working with Excel spreadsheets ; Working with Google sheets ; Working with PDF and Word documents ; Working with CSV files and JSON data ; Keeping time, scheduling tasks, and launching programs ; Sending email and text messages ; Manipulating images ; Controlling the keyboard and mouse with GUI automation -- Appendix A: Installing third-party modules -- Appendix B: Running programs -- Appendix C: Answers to the practice questions
Keywords: Python (Computer program language); Computer programming; Software